Activation of adenovirus 5 E1A transcription by region E1B in transformed primary rat cells. - Jochemsen, A G (1987)
The human adenovirus 5 E1A region can immortalize primary cultures of baby rat kidney cells, but requires the presence of the E1B region for complete oncogenic transformation. One of the effects of the E1B region in the transformation process is the activation of E1A expression. We have investigated the mechanism of this stimulation of E1A expression using nuclear run-on assays with nuclei from Ad5 E1A- and Ad5 E1-transformed cells. It was found that E1B enhances E1A at the level of transcription-initiation. This activation is mainly observed when the E1A and E1B regions are integrated simultaneously into the cellular genome and only minimally when these genes are integrated separately, strongly suggesting that a close physical linkage of these regions is essential for the observed effect.